2022
DOI: 10.1002/path.5893
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunosuppressive factors in retinoblastoma cell secretomes and aqueous humor from patients

Abstract: The microenvironment of retinoblastoma, the solid malignancy of the developing retina, is immunosuppressive. To study the interactions between tumor‐associated microglia/macrophages (TAMs) and tumor cells in retinoblastomas, we analyzed immunohistochemistry markers in 23 patient samples and characterized 105 secreted cytokines of 11 retinoblastoma cell models in culture. We detected profuse infiltration of CD163+ protumoral M2‐like polarized TAMs in eyes enucleated due to cancer progression. Previous treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Our finding of MIF to be highly expressed in active RB agrees with the results of a recent study showing that this protein, among others, is likely involved in the production of an immunosuppressive microenvironment in these intraocular tumors [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of MIF to be highly expressed in active RB agrees with the results of a recent study showing that this protein, among others, is likely involved in the production of an immunosuppressive microenvironment in these intraocular tumors [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, several studies have reported that cell free DNA isolated from the AH of enucleated or conservatively treated eyes with RB can be used to characterize the genetics of the disease [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], and it may also correlate with clinical outcomes [ 14 , 15 , 16 ]. On the other hand, the modulation of several proteins has been described in AH obtained after enucleation [ 17 , 18 , 19 , 20 , 21 , 22 ] or collected from patients who underwent intravitreal chemotherapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells reprogram TAMs to promote immune suppression and resistance to anti-tumor drugs. This is supported by studies demonstrating that macrophages cultured in a conditioned medium obtained from retinoblastoma cells exhibit a more pro-tumor M2 phenotype [ 27 , 28 ]. M2-type TAMs are associated with various other types of pediatric tumors, including osteosarcoma, rhabdomyosarcoma, leukemia, lymphoma, and brain tumors.…”
Section: Profiling the Immune Microenvironment Of Pediatric Tumorsmentioning
confidence: 79%
“…Similarly, in retinoblastoma, the microenvironment is enriched with pro-tumorigenic macrophages expressing the M2-type microglial marker Iba1+ [ 27 ]. The population of these TAMs increases after therapy [ 27 ]. Tumor cells reprogram TAMs to promote immune suppression and resistance to anti-tumor drugs.…”
Section: Profiling the Immune Microenvironment Of Pediatric Tumorsmentioning
confidence: 99%
“…All cultures were under passage 20. As a quality control, we determined the short tandem repeat profiles of the primary cells, which we reported elsewhere [ 17 ].…”
Section: Methodsmentioning
confidence: 99%